2017
DOI: 10.1088/1475-7516/2017/09/008
|View full text |Cite
|
Sign up to set email alerts
|

Getting super-excited with modified dispersion relations

Abstract: We demonstrate that in some regions of parameter space, modified dispersion relations can lead to highly populated excited states, which we dub as "super-excited" states. In order to prepare such super-excited states, we invoke dispersion relations that have negative slope in an interim sub-horizon phase at high momenta. This behaviour of quantum fluctuations can lead to large corrections relative to the Bunch-Davies power spectrum, which mimics highly excited initial conditions. We identify the Bogolyubov coe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…In order to have a stable vacuum in the deep UV, where the dispersion relation is dominated by the k 6 , we consider β 0 > 0 7 . If Hubble crossing takes place when ω 2 ∼ k 2 , transitions between regions with a different dispersion relation can lead to excited initial states [7]. In this case, if α 0 < 0, one can have relatively large corrections, much bigger than one, compared to the standard inflationary predictions for the two point function.…”
Section: Scalar Perturbationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to have a stable vacuum in the deep UV, where the dispersion relation is dominated by the k 6 , we consider β 0 > 0 7 . If Hubble crossing takes place when ω 2 ∼ k 2 , transitions between regions with a different dispersion relation can lead to excited initial states [7]. In this case, if α 0 < 0, one can have relatively large corrections, much bigger than one, compared to the standard inflationary predictions for the two point function.…”
Section: Scalar Perturbationsmentioning
confidence: 99%
“…On the other hand, if α 0 < 0, there could be large modulation factors on the power spectrum. In [7], we focused on the range of parameters for α 0 and β 0 such that…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…The scheme was originally motivated by the studies in condensed matter physics that suggested departure from Lorentzian dispersion relation beyond some momentum cutoff [14,15]. It was shown in [16] that two formalisms of excited initial state and MDR could be related to each other and how a range of possibilities that arise within the excited state setup, appears in the formalism of MDR by changing the functional behavior and/or the coefficients of the dispersion relation. Although in the study of the new physics on inflationary observables, the MDRs were introduced in the setup of the cosmological perturbation theory through some ad hoc condensed matter procedure, with the advent of the Effective Field Theory of Inflation (EFToI) [17] and HořavaIt-Lifshitz gravity [18,19], such MDRs found a clear origin within the field of high energy physics.…”
Section: Introductionmentioning
confidence: 99%